You are on page 1of 4

# MATH 233 MULTIVARIABLE CALCULUS

## Project 2: The Wave Equation

Stephen Yan
October 16, 2012
(1)
u
t t
u
xx
=0 may be rewritten as

2
u
t
2

2
u
x
2
=0
u
t
=
u
t
= f (x +t ) g(x t ) u
t t
=

2
u
t
2
= f (x +t ) +g(x t )
u
x
=
u
x
= f (x +t ) +g(x t ) u
xx
=

2
u
x
2
= f (x +t ) +g(x t )
u
t t
u
xx
= f (x +t ) +g(x t ) [ f (x +t ) +g(x t )] =0
(2)
We set up the system:
f (x) +g(x) =u
0
f

(x) g

(x) =u
1
knowing that u(0, x) =u
0
and u
t
(0, x) =u
1
Recall the Fundamental theorem of calculus:
If F(x) =
_
x
a
f (t ) dt then F

(x) = f (x) given that f is continuous and real on a closed interval [a, b]
Thus f (x)g(x) =
_
x
0
u
1
(y) dy +c where y is treated as a dummy variable, c is an arbitrary constant, and
u
1
=( f g)

(x)
1
We can manipulate the system, and nd that g(x) =u
0
f (x) and then substitute into the
above equation to arrive at:
f (x)[u
0
f (x)] =
_
x
0
u
1
(y) dy 2f (x) =u
0
(x)+
_
x
0
u
1
(y)dy f (x) =
1
2
u
0
(x)+
1
2
_
x
0
u
1
(y) dy +
c
2
Similarly, we nd that g(x) =
1
2
u
0
(x)
1
2
_
x
0
u
1
(y)dy
c
2
Recall that u(t , x) = f (x +t ) +g(x t )
Substituting for f and g we nd u(t , x) in terms of u
0
and u
1
to be
1
2
u
0
(x +t ) +
1
2
_
x+t
0
u
1
(y)dy +
c
2
+
1
2
u
0
(x t )
1
2
_
xt
0
u
1
(y)dy
c
2
simplifying to
1
2
_
u
0
(x +t ) +u
0
(x t ) +
_
x+t
xt
u
1
(y)dy
_

_

_
xt
0
u
1
(y) dy =
_
0
xt
u
1
(y) dy
_
An odd function is dened byf (x) =f (x)
Observing u(t , 0) to be
1
2
_
u
0
(t ) +u
0
(t ) +
_
t
t
u
1
(y)dy
_
we rewrite it knowing it is odd as
1
2
_
u
0
(t ) u
0
(t ) +
_
t
t
u
1
(y)dy
_
=
1
2
_
t
t
u
1
(y)dy
This evaluates to
1
2
_
u
1
(t ) [u
1
(t )]
_
Because it is odd and thus anti-symmetric,
u
1
(t ) =u
1
(t ) and is thus 0, satisfying the wave equation.
Similarly, we nd u(t , 1) to be
1
2
_
u
0
(1+t ) +u
0
(1t ) +
_
1+t
1t
u
1
(y) dy
_
We can eliminate the u
0
terms knowing that the function is odd and they are opposites and
be left with
_
1+t
1t
u
1
(y) dy =
_
1
1t
u
1
(y) dy +
_
1+t
1
u
1
(y) dy
A periodic function is dened by f (x +k) = f (x) where k is some integer (in this case 1).
Let z = y +2k and dz =dy as u
0
and u
1
are periodic with periods of 2.
Thus
_
1
1t
u
1
(y) dy =
_
1
1t
u
1
(y +2k) dy =
_
1
1t
u
1
(z) dz
We nd that
_
1
1t
u
1
(z) dz+
_
1
1t
u
1
(y) dy =0 because of periodicity, satisfying the wave equation.
2
(3)
If u and u are solutions to E, then we assert that u= u or alternatively:
u u =0
Using this fact, we can also dene boundary conditions for w(t , x)
_

_
w
t
=u
t
u
t
w
t t
=u
t t
u
t t
w
x
=u
x
u
x
w
xx
=u
xx
u
xx
w
t t
w
xx
=[u
t t
u
t t
] [u
xx
u
xx
] =0
w(t , 0) =u(t , 0) u(t , 0) =0
w(t , 1) =u(t , 1) u(t , 1) =0
w(0, x) =u(0, x) u(0, x) =u
0
(x) u
0
(x) =0
w
t
(0, x) =u
t
(0, x) u(0, x) =u
1
(x) u
1
(x) =0
Knowing these conditions, we can proceed to differentiate E(t ) =
_
1
0
(w
2
t
+w
2
x
) dx
E

(t ) =
_
1
0
(2w
t
w
t t
+2w
x
w
t x
) dx
We can break this into separate parts as 2
__
1
0
w
t
w
t t
dx +
_
1
0
w
x
w
t x
dx
_
We can integrate the second component using integration by parts. Recall that for some
product of two functions,
_
udv =uv
_
v dv
For
_
1
0
w
x
w
t x
dx Let
u =w
x
du =w
xx
dx
dv =w
t x
dx v =w
t
Thus
_
1
0
w
x
w
t x
dx =w
x
w
t

1
0

_
1
0
w
t
w
xx
dx
We nd that the value w
x
w
t

1
0
is 0 because w(t , 0) =0 and w(t , 1) =0 from our boundary
conditions.

_
1
0
w
x
w
t x
dx =
_
1
0
w
t
w
xx
dx
We can re-substitute this into the original separated E

(t ) and nd that E

(t ) =2
_
_
1
0
w
t
w
t t
w
t
w
xx
dx
_
3
2
_
1
0
w
t
(w
t t
w
xx
) dx
We know w
t t
w
xx
to be 0, integrating the argument gives 0 E

(t ) =0
Thus we know E(t ) to be a constant and E(t ) =E(0), implying that w(t , x) =0 for all t since
w is a component of the derivative of E.